PENGARUH PENGETAHUAN DAN KESADARAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DENGAN SANKSI PERPAJAKAN SEBAGAI VARIABEL MODERATING (Studi Pada Kantor SAMSAT Wilayah I Kota Makassar) - Andi Marlinah (AkMen JURNAL ILMIAH, 2018)
This research aims to examine the effect of knowledge and awareness on taxpayer complience in paying vechile tax in SAMSAT office area I Makassar city with sanction as moderating variable. The research data was obtained from questionnaires (primary) by taking as many as 100 respondents taxpayer.The analysis data was used by Moderated Regression Analysis (MRA) with SPSS 24.0. These result of research showed that knowledge and conscious have a positive effect on compliance tax, sanctions can’t moderate the relationship between knowledge on taxpayer compliance, and sanctions can’t moderate the relationship between conscious of motor vehicle taxpayer compliance.